Automation application when forming the consolidated financial statements of holding - A. V. Busigina (Путеводитель предпринимателя)
In article the order of formation of the consolidated financial statements of holding on the basis of the international standards of the financial reporting is considered. Proposals related to the formation of the consolidated financial statements of corporations are contained in a number of publications, however, the adoption of new regulations, causing the need for more research problem.